Cognitive impairment in patients with migraine: causes, principles of effective prevention and treatment - V. A. Golovacheva; K. A. Pozhidaev; A. A. Golovacheva (Неврология, нейропсихиатрия, психосоматика)
Cognitive impairment (CI) is common in patients with migraine; its causes and pathogenesis continue to be discussed. Some authors consider that migraine proper does not lead to decreased cognitive functions, neuroimaging changes in the brain white matter are asymptomatic in migraine; and CI in patients with this condition is caused by comorbidities (depression, anxiety disorder) and/or concurrent cerebrovascular and neurodegenerative diseases. Other authors report the pathogenetic role of migraine in the development of CI and the importance of the frequency of headache attacks and neuroimaging changes in the brain matter in migraine. The paper reviews clinical trials dealing with the prevalence, causes, and pathogenesis of CI in patients with migraine. It sets forth the current principles of prevention and treatment of CI in patients with this condition.